1976
DOI: 10.1016/s0022-5347(17)58860-6
|View full text |Cite
|
Sign up to set email alerts
|

The Seminoma Decoy: Measurement of Serum Human Chorionic Gonadotropin in Patients with Seminoma

Abstract: Serum human chorionic gonadotropin levels were determined in 20 patients with histologically proved seminoma. The test was positive in 2 of the 20 patients and was predictive of non-seminomatous metastasis in each case. Serum human chorionic gonadotropin is a useful tumor marker in detecting and following non-seminomatous metastases in men with pure seminoma of the testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 3 publications
2
8
0
3
Order By: Relevance
“…These exist in pure choriocarcinomatous tumors with choriocarcinomatous components and in seminomas [7], Marker sensitivity is assumed to in crease with stage [9], In 4 of 12 cases of patients with seminoma there was an increase of P-HCG, and 1 patient had an elevated HCG-p. Other authors have described pathological HCG values in 6-24% of seminomas [1,3,5,6]. In 58 patients with nonseminomatous tumors, we found the highest sensitivity for HCG-p. Sera from 27 patients out of 56 had increased levels whereas P-HCG measurements re sulted in 20 elevated cases out of 56.…”
Section: Discussionsupporting
confidence: 53%
“…These exist in pure choriocarcinomatous tumors with choriocarcinomatous components and in seminomas [7], Marker sensitivity is assumed to in crease with stage [9], In 4 of 12 cases of patients with seminoma there was an increase of P-HCG, and 1 patient had an elevated HCG-p. Other authors have described pathological HCG values in 6-24% of seminomas [1,3,5,6]. In 58 patients with nonseminomatous tumors, we found the highest sensitivity for HCG-p. Sera from 27 patients out of 56 had increased levels whereas P-HCG measurements re sulted in 20 elevated cases out of 56.…”
Section: Discussionsupporting
confidence: 53%
“…Our major interest was whether an improved specificity due to two monoclonal anti bodies correlated with improved sensitivity, and if the test was suitable for monitoring seminoma treatment [14][15][16]. Furthermore, the possible prognostic value of ele vated ß-hCG levels in pure seminoma was of special inter-…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Pure seminoma re quires radiotherapy in stages I, Ha, and lib; whereas stages lie (bulky disease), III, and IV, as well as nonseminomatous tumors are primarily treated by chemotherapy [9,23,24], ß-hCG and AFP are helpful markers for distin guishing between seminomatous and nonseminomatous tumors. ß-hCG, a glycoprotein, may be synthesized in both syncytiotrophoblastic giant cells and undifferen tiated teratomas, whereas AFP is produced by nonsemi nomatous tumors only [14,[25][26][27][28][29]36], Low ß-hCG serum levels are seen in both seminoma tous and nonseminomatous testicular cancer (< 200 IU/1). These findings influence therapy [21] considerably.…”
Section: Measurement Of Tumor Markersmentioning
confidence: 99%
“…Cochran [12] reported similar results, whereas Javadpour et al [13] and Bartsch and Scheiber [14] found multinuclear giant cells in seminoma for immunoreactive HCG.…”
Section: Patients With Seminomatous Testis Tumorsmentioning
confidence: 80%